Effects of digital health interventions on muscle mass, muscle strength, and physical function in older adults with sarcopenia: a systematic review and meta-analysis - Chen, Wenjia; Yao, Jiayi; Wang, Haozhe; Jia, Shiguan; Zhu, Xueqiang; Mao, Lihong (Frontiers in Public Health, 2025)
Background and aimsSarcopenia, an age-related progressive muscle disorder, is characterized by low muscle strength. While digital health technologies are emerging as a management tool, systematic evidence of their comprehensive effects on older adults diagnosed with sarcopenia is lacking. We therefore aimed to comprehensively evaluate the effects of digital health interventions (DHIs) on muscle mass, muscle strength, physical function, and quality of life in this specific population.MethodsWe systematically searched PubMed, Embase, Web of Science, and the Cochrane Library for randomized controlled trials (RCTs) published up to 13 September 2025. Eligible patients were aged ≥60 years with a formal diagnosis of sarcopenia. We conducted a meta-analysis to assess intervention effects and used the GRADE system to assess the certainty of evidence.ResultsEleven RCTs with a total of 757 patients were included. The meta-analysis revealed that DHIs significantly improved skeletal muscle mass [Standardized Mean Difference (SMD) = 0.35, 95% CI: 0.13–0.57] and grip strength (SMD = 0.28, 95% CI: 0.04–0.53). However, improvements in physical function were selective, while indicators such as sit-to-stand time improved, no significant effects were found for gait speed, walking distance, or activities of daily living (ADL). The effect on quality of life (QoL) was uncertain. The certainty of evidence was moderate for skeletal muscle mass and low for grip strength.ConclusionDigital health interventions appear effective in improving muscle mass and muscle strength in older adults with sarcopenia, though their impact on physical function is selective. Technologies that provide real-time interaction and personalized feedback, particularly those based on artificial intelligence (AI) and virtual/mixed reality (VR/MR), are promising, although current evidence is preliminary. From a public health standpoint, the scalability and accessibility of DHIs represent a valuable supplementary strategy for sarcopenia management.Systematic review registrationwww.crd.york.ac.uk/prospero, identifier CRD420251151435.